Revolutions of Resolution - Joaquin Zerené Harcha; Paula Cardoso Pereira (tripleC: Communication, Capitalism & Critique)
Digital technologies have profoundly transformed the process of production and transmission of visual information and images. From a critical perspective on visual culture this article proposes an analysis of low-resolution digital images, here treated as poor images (Steyerl), in today’s “class society of images”. Resolution refers to a material dimension of images that needs to be explored. A critical approximation to the role of poor images in today’s transnational and global communication asks for a focus on their modes of circulation, politics of accessibility and property rights as well as on the role of materiality in the economy of contemporary visual culture.